2019
DOI: 10.17073/0021-3438-2019-6-51-59
|View full text |Cite
|
Sign up to set email alerts
|

Development, modeling and research of technology for producing longish deformed semi-finished products from aluminum-magnesium alloys with low scandium contents

Abstract: The paper provides the results of studying the technology for producing longish deformed semi-finished products by sheet rolling and direct rolling-extruding of aluminum-magnesium alloys with different scandium contents. Computer and physical modeling methods were used for the research and the results were verified by pilot tests. These alloys were selected for the research due to the fact that Al–Mg aluminum alloys doped with scandium have increased corrosion resistance along with their high strength. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In actual production, you can cut a certain size of corrugated board with a paper cutter and then weigh it. Generally, before production, the theoretical quantity of corrugated board can be estimated according to the raw materials used, that is, G � 􏽘 g 1 + 􏽘 g m c + 􏽘 g j + 􏽘 g a , (6) where G is the quantity of corrugated board in g/m 2 , g 1 , g m , g j , g a are the consumption of a box of board paper, corrugated base paper, laminated paper, and adhesive in g/ m 2 , and Y is the corrugated coefficient. By comparing the theoretical quantitative results with the actual measured results, we can analyze the problems existing in the quality and shape of base paper [27].…”
Section: Experiments and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In actual production, you can cut a certain size of corrugated board with a paper cutter and then weigh it. Generally, before production, the theoretical quantity of corrugated board can be estimated according to the raw materials used, that is, G � 􏽘 g 1 + 􏽘 g m c + 􏽘 g j + 􏽘 g a , (6) where G is the quantity of corrugated board in g/m 2 , g 1 , g m , g j , g a are the consumption of a box of board paper, corrugated base paper, laminated paper, and adhesive in g/ m 2 , and Y is the corrugated coefficient. By comparing the theoretical quantitative results with the actual measured results, we can analyze the problems existing in the quality and shape of base paper [27].…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…According to Yu and Sinigh, the output value of corrugated paper industry in China has also surpassed that of the packaging industry in the world since 2003. Sidelnikov and others found that, in addition to the increasing share of paper packaging in various packaging materials, paper packaging is also developing in the direction of high quality, high strength, lightweight, and versatility, which have also become an important reason for the rapid and stable development of paper packaging industry in the packaging field [6]. With the rapid and stable development of the paper packaging industry, Deja and others have also been widely used in all walks of life in order to meet the needs of multi-Wu chemical industrial design outside China and fully meet the market development needs of small batch, personalization, interest, diversification, and short cycle, it has become a key technology to improve the product R&D capability and enhance competitiveness of various enterprises [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The simulation results showed that during hot rolling of large-sized ingots, a change in the geometry of the roll is observed (Fig. 2), and a more intense deformation of the surface layers is realized as compared to the central ones, which leads to different velocities of the outflow of metal layers and the appearance of tensile stresses [4]. Simulation of the cold rolling process (Fig.…”
Section: Materials and Methods Of Carrying Out Researchesmentioning
confidence: 98%
“…Engineering products, especially aircraft and shipbuilding, widely use structural products made by machining aluminum alloy plates obtained by hot and cold sheet rolling [1][2][3][4][5][6]. One of the important tasks is to develop rolling modes that exclude the formation of various defects that arise due to the temperature heating of the metal during its deformation and the action of tensile stresses in the surface and intermediate zones along the thickness of the rolled product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation